The Importance of User Education As An Effort to Maximize the Use of Library At SMKN 1 Bandung - Sri Aprianti, Nenden; Rullyana, Gema; Syafitri, Nanda Khaerunnisa (Ilmu Informasi Perpustakaan dan Kearsipan, 2022)
User education is material about libraries that are given to users. Libraries provide user education so that users know how to use the library. There are still users who do not understand using the library, which makes the writer interested in researching the importance of user education to maximize the use of the library at SMKN 1 Bandung. This study uses a descriptive method with a quantitative approach, where data is obtained using a questionnaire distributed using google forms. The population in this study were users of SMKN 1 Bandung, which amounted to 30 users. The study results revealed that user education in the library of SMKN 1 Bandung was carried out by providing various methods of user education for school residents. Pustaka revealed that user education provided by the library of SMKN 1 Bandung is considered essential and helps users use or utilize various library services and facilities.